Great Myths of Economics - Boivin, Jean (Relations industrielles / Industrial Relations, 1968)
This article reviews "Great Myths of Economics" by Dan Paarlberg.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Economy : Organization and Development - Boivin, Jean (Relations industrielles / Industrial Relations, 1968)
This article reviews "The Canadian Economy : Organization and Development" by Ian M. Drummond.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z